1982
DOI: 10.2118/8430-pa
|View full text |Cite
|
Sign up to set email alerts
|

Entrainment and Deposition of Fine Particles in Porous Media

Abstract: Entrainment and redeposition of naturally occurring fine particles in porous media has been suggested as a mechanism leading to abnormal decline in productivity of producing wells. This paper describes the results of studies conducted to determine factors affecting this phenomenon. Experimental work done as part of this study provides the basis for a proposed phenomenological theory of entrainment and deposition. The central concept of this theory is representation of both particle and pore size distributions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
292
0
7

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(308 citation statements)
references
References 11 publications
9
292
0
7
Order By: Relevance
“…Considering all the experimental results, it should be emphasized that the core plugging effects observed with several asphaltenic crudes exhibit very similar trends, both in reducing permeability and accumulating in situ deposits with core damage results from the migration of fine-grained solid particles accompanying brine flow through the porous medium [18,19,20].…”
Section: Mechanisms and Interpretation Of Core Plugging Experimentsmentioning
confidence: 78%
“…Considering all the experimental results, it should be emphasized that the core plugging effects observed with several asphaltenic crudes exhibit very similar trends, both in reducing permeability and accumulating in situ deposits with core damage results from the migration of fine-grained solid particles accompanying brine flow through the porous medium [18,19,20].…”
Section: Mechanisms and Interpretation Of Core Plugging Experimentsmentioning
confidence: 78%
“…It should be mentioned here that the fine particles released consist of clay, quartz and feldspar [74]. Furthermore, the flow velocity is higher.…”
Section: Hydrodynamically Induced Releasementioning
confidence: 91%
“…In such cases, Rege and Fogler [83] have shown that the higher the overlap between the size distribution of fines and that of pore constrictions, the higher is the extent of plugging and vice versa. Table 3 presents some qualitative results on whether plugging or other possible types of deposition would possibly occur as determined by the ratio of the size of fines to size of the pore constrictions [74,84].…”
Section: Size Of Colloidal Finesmentioning
confidence: 99%
“…The above three equations are adopted as the governing equations for the erosion within soils. The eroded soil particles can redeposited during their travel, but the redeposition process is ignored in this study since there is experimental evidence that redeposition can be ignored for small concentrations of soil particles in pore streams typical of natural subsurface systems (Gruesbeck and Collins, 1982;Reddi and Bonala, 1997). From an engineering viewpoint, it has been claimed that a consideration of redeposition may lead to an underestimation of soil erosion, which means that soil structures can be put at risk of deterioration.…”
Section: Derivation Of the Governing Equationsmentioning
confidence: 99%